Impaired gastric and urinary but preserved cardiac interoception in women with endometriosis - Chiara Cantoni; Sofia Ciccarone; Maria Grazia Porpora; Salvatore Maria Aglioti (PLoS ONE, 2025)
Endometriosis is a chronic inflammatory gynaecological condition frequently associated with chronic pelvic pain. Visceral hypersensitivity could be present, like in other chronic pain conditions, causing altered levels of interoception. So far, studies have explored interoceptive deficits in chronic pain individuals mainly using questionnaires or cardiac interoceptive accuracy tasks. Here, we explore the cardiac, gastric, and urinary domains to probe interoceptive differences between patients with endometriosis and healthy women. 30 patients and 30 controls underwent three interoceptive tasks for assessing the cardiac domain (using the Heartbeat Counting Task, HCT), the gastric domain (using the Water Load Test-II, WLT-II) and the bladder domain (using a novel Urinary Interoceptive Task, UIT). Participants also completed bladder interoceptive beliefs measures and subjective pain ratings for each endometriosis symptom (dysmenorrhea, dyspareunia, dyschezia, chronic pain). A positive correlation between the WLT-II and the UIT emerged in all participants (R = 0.47, p < 0.001), indicating that the lower the gastric interoceptive abilities, the lower the urinary ones. Moreover, compared to healthy controls, women with endometriosis exhibited lower scores in the WLT-II (t(58) = 4.6814, p < 0.001) and the UIT (t(39.931)= 5.1462, p < 0.001), as well as higher scores in the subjective bladder beliefs questions (t(57.346)= -4.0304, p < 0.001). Results indicate a dissociation between patients’ poor objective performance on interoceptive tasks and their high bladder interoceptive beliefs. UIT scores were associated with pain symptoms, suggesting that patients, probably due to sensitisation, struggle to ignore discomfort sensations, resulting in reduced accuracy in detecting physiological signals coming from the pelvic area.